The Hierarchical Divide of Global South: Rohingya and Bangsamoro as Southeast Asian Subaltern - Kusumadewi, Hemalia (Institute of International Studies, 2025)
This paper attempts to understand the contemporary discourse of subalternity and global south, particularly through the lens of Southeast Asian marginalized muslim communities, the Bangsamoro of Philippines and Rohingya of Myanmar. This is to understand the deeper hierachal divide within the Global South that threaten the ‘South Solidarity’, and straying away from the mainstream North-South discussion. his paper identify those groups as ‘subaltern of the subaltern’, a smaller group of subalter who has been systematically discriminated by the larger or more dominant group. This research employs the concept of Subalternity to understand on what basis a group is assigned the identity of being a subaltern, and understanding the discussion of Subalternity in the field of International Relations studies. This research employs literature review as its primary methodology. This paper finds a deeper hierarchal divide withing countries of Global South which manifests in communities coined as ‘subaltern of subaltern’, or those who are marginalized within Global South. This implication casts doubts upon the sustainability of the ‘South Solidarity’ agenda.This paper attempts to understand the contemporary discourse of subalternity and global south, particularly through the lens of Southeast Asian marginalized muslim communities, the Bangsamoro of Philippines and Rohingya of Myanmar. This is to understand the deeper hierachal divide within the Global South that threaten the ‘South Solidarity’, and straying away from the mainstream North-South discussion. his paper identify those groups as ‘subaltern of the subaltern’, a smaller group of subalter who has been systematically discriminated by the larger or more dominant group. This research employs the concept of Subalternity to understand on what basis a group is assigned the identity of being a subaltern, and understanding [A1] [A2] the discussion of Subalternity in the field of International Relations studies. This research employs literature review as its primary methodology. This paper finds a deeper hierarchal divide withing countries of Global South which manifests in communities coined as ‘subaltern of subaltern’, or those who are marginalized within Global South. This implication casts doubts upon the sustainability of the ‘South Solidarity’ agenda. [A1]Check typo [A2]